2002
DOI: 10.2165/00007256-200232080-00002
|View full text |Cite
|
Sign up to set email alerts
|

Training Techniques to Improve Endurance Exercise Performances

Abstract: In previously untrained individuals, endurance training improves peak oxygen uptake (V. O2peak), increases capillary density of working muscle, raises blood volume and decreases heart rate during exercise at the same absolute intensity. In contrast, sprint training has a greater effect on muscle glyco(geno)lytic capacity than on muscle mitochondrial content. Sprint training invariably raises the activity of one or more of the muscle glyco(geno)lytic or related enzymes and enhances sarcolemmal lactate transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
73
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 137 publications
7
73
1
5
Order By: Relevance
“…Our finding that Vo 2peak improved by 7.0% following HIT is in agreement with previous research in runners, swimmers, and cyclists 17 and is likely to be the main contributing factor in the greater performance improvement following HIT. Several studies have shown an increase in Vo 2peak of 5% to 15%, following various HIT methods.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding that Vo 2peak improved by 7.0% following HIT is in agreement with previous research in runners, swimmers, and cyclists 17 and is likely to be the main contributing factor in the greater performance improvement following HIT. Several studies have shown an increase in Vo 2peak of 5% to 15%, following various HIT methods.…”
Section: Discussionsupporting
confidence: 92%
“…While there is limited research regarding the effects of HIT on TT performance in rowers, other studies have shown improvements in running and cycling time trial performance following HIT. 17 A comprehensive review on HIT 3 has shown performance improvements of between 3% to 8.3% following interval training at maximal and supramaximal intensities. In runners, HIT has been associated with ~3% improvements in 5-km 20 and 10-km 21 running times in middleand long-distance runners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle contraction during exercise induces a cascade of cardiovascular and muscoskeletal adaptations resulting in improved delivery and utilization of oxygen and nutrients in the working muscles (Taivassalo et al, 2000), thus, enhancing exercise endurance (Kubukeli et al, 2002). EODF-induced increase in running distance could be related to modifications in lipid and protein metabolism subsequent to increased corticosterone levels (Challet et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…HIIT has long been used in the athletic setting as a means of enhancing physical performance, [41][42][43][44][45][46] but only more recently in the clinical context for the prevention and management of chronic disease. Thus, the utility of HIIT, relative to MICT, in ameliorating the specific symptoms and adverse effects of those at risk of or afflicted with CVD is not well understood.…”
mentioning
confidence: 99%